2022
DOI: 10.3390/membranes13010032
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Poly(Lactic Acid)/Poly (ethylene glycol)-Poly(propyl glycol)-Poly(ethylene glycol) Blended Nanofiber Membranes for Fog Collection

Abstract: Fog is a resource with great potential to capture fresh water from the atmosphere, regardless of the geographical and hydrological conditions. Micro-sized fog collection requires materials with hydrophilic/phobic patterns. In this study, we prepared hydrophilic poly(lactic acid) (PLA)/poly(ethylene glycol)-poly(propyl glycol)-poly(ethylene glycol) (PEG-PPG-PEG) blended nanofiber membranes with various PEG-PPG-PEG concentrations by electrospinning. Changes in the morphological and chemical properties, surface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…To address the hydrophobic nature and low biocompatibility of PLA blends, PEG was utilized. Toncheva et al revealed that PEG incorporation by physical blending or chemical grafting did not significantly modify the surface wettability of the PLA electrospun mats [ 50 ]. Otherwise, further research established proved that blending PEG into a PLA solution is a successful strategy to increase the hydrophilicity of PLA electrospun membranes.…”
Section: Discussionmentioning
confidence: 99%
“…To address the hydrophobic nature and low biocompatibility of PLA blends, PEG was utilized. Toncheva et al revealed that PEG incorporation by physical blending or chemical grafting did not significantly modify the surface wettability of the PLA electrospun mats [ 50 ]. Otherwise, further research established proved that blending PEG into a PLA solution is a successful strategy to increase the hydrophilicity of PLA electrospun membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The PLA and PEG-PPG-PEG solutions were initially prepared separately. First, 12.5% ( w / v ) of PLA powder was dissolved in DCM at 50 °C for 1 h, and then 9% ( w / v ) of PEG-PPG-PEG powder was dissolved in DMF at 50 °C for 30 min [ 17 ]. After preparing each solution, both the solutions were blended in the 4:1 ratio for PLA and PEG-PPG-PEG solutions, respectively, and kept for 12 h of stirring to prepare an absolutely homogenized solution.…”
Section: Methodsmentioning
confidence: 99%
“…On a super hydrophilic surface, water tends to form a thin film rather than droplets [ 16 ], which helps the adsorbent to capture the maximum amount of pollutants on its surface. PLA’s surface is highly hydrophobic, although many surface and bulk changes have been found to improve hydrophilicity; thus, coating, grafting, and blending PLA with more hydrophilic polymers is used to modify the surfaces of PLA [ 17 ]. An important factor needs to be taken into account when using biopolymer as an adsorber.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most researchers only focused on the directional transportation of water on fibers. 113 However, in the five years, some groups focused on the reversibly directional movement of tiny droplets. Liu et al designed a type of spindle-knot with HS via the double dip-coating technique in 2017.…”
Section: The Development Of Fog Collection With Hierarchically Struct...mentioning
confidence: 99%